Development of Digital Green Waqf for Social Sustainability in Riau, Indonesia - Wali Saputra (Indo Publishing, 2025)
This scholarly investigation endeavors to formulate a digital green waqf model that underpins social sustainability within the Riau Province, employing a qualitative methodology. Through comprehensive interviews conducted with ten informants, which include nadzir waqf, scholars, government officials, notable public figures, and practitioners in sharia fintech, the research scrutinized the comprehension, obstacles, advantages, developmental strategies, and anticipations and recommendations pertaining to digital green waqf. The findings indicate that digital green waqf possesses significant potential to enhance community engagement, particularly among the youth demographic, as well as to foster transparency and efficacy in waqf administration. Nevertheless, considerable impediments exist in the form of inadequate digital literacy, infrastructural deficiencies, and regulatory frameworks that remain non-adaptive. The proposed developmental strategies encompass the enhancement of educational and training programs, fortification of infrastructure, fostering synergies among multiple stakeholders, and the adoption of transparent technologies grounded in sharia principles. The study concludes that digital green waqf may serve as an innovative remedy for the socially and environmentally sustainable management of waqf in Riau, contingent upon comprehensive backing from diverse stakeholders.